2018 20th International Conference on Transparent Optical Networks (ICTON) 2018
DOI: 10.1109/icton.2018.8473650
|View full text |Cite
|
Sign up to set email alerts
|

Giant Rydberg Excitons in Synthetic and Artificial Cuprous Oxide

Abstract: High-lying Rydberg states of Mott-Wannier excitons are receiving considerable interest due to the possibility of adding long-range interactions to the physics of exciton-polaritons. Here, we study Rydberg excitation in bulk synthetic cuprous oxide grown by the optical float zone technique and compare the result with natural samples. X-ray characterization confirms both materials are mostly single crystal, and mid-infrared transmission spectroscopy revealed little difference between synthetic and natural materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…10 the second location was slightly red-shifted relative to those at the first location. This confirmed our previous absorption measurements [33] that showed the crystalline environment varying slightly across the sample and giving rise to subtle but measurable changes in peak energies. However, although the amplitudes and widths of the peaks changed dramatically in the spectrum at the new location, the rapid drop to zero of the SHG signal above n = 12 was still present.…”
Section: Spatially Resolved Two-photon Spectroscopysupporting
confidence: 90%
See 4 more Smart Citations
“…10 the second location was slightly red-shifted relative to those at the first location. This confirmed our previous absorption measurements [33] that showed the crystalline environment varying slightly across the sample and giving rise to subtle but measurable changes in peak energies. However, although the amplitudes and widths of the peaks changed dramatically in the spectrum at the new location, the rapid drop to zero of the SHG signal above n = 12 was still present.…”
Section: Spatially Resolved Two-photon Spectroscopysupporting
confidence: 90%
“…Previous experiments have also shown that the visibility of high-n excitons varies locally even in the highest quality samples, with some regions of the sample exhibiting both stronger lines and a higher maximum value of n [21]. We have previously shown [33] that our natural samples exhibit variation in the exciton spectrum on a length scale of tens of µm. Therefore, we exploited the spatial resolution of our SHG spectroscopy setup to measure the SHG spectrum and the SHG intensity at different locations across the sample.…”
Section: Spatially Resolved Two-photon Spectroscopysupporting
confidence: 62%
See 3 more Smart Citations